Inquiry into Understanding the Concept of Common Fraction among Lithuanian Students - Būdienė, Virginija (Acta Paedagogica Vilnensia, 2005)
The article deals with the survey of understanding of a concept of common fraction among 14-year-old Lithuanian students. The model of concept understanding verification is introduced and used to analyse the survey data. Data from Third International Mathematics and Science Study (TIMSS) is used for analysis. The analysis of data, using the proposed model of verification of understanding of concepts, identifies that less than 50 percent of 14-year old Lithuanian students perceive the concept of common fraction in a right way. The causes of the problem are analysed in the article. Possible extensions of application area of the verification model are discussed.